Determination of the Child's Nasab in Li'an Cases Through DNA Test in the Opinion of Sheikh Yusuf Al-Qaraḍawi - Riady, Ahmad; Chandra, Age Surya Dwipa (Universitas Islam Negeri Raden Intan Lampung, 2024)
In li'an cases, children often become victims of serious adverse effects after li'an itself, including emotional trauma and legal uncertainty. Starting from this problem, this paper will explain how Sheikh Yusuf Al-Qaraḍawi's opinion on determining the child's lineage through DNA testing in the context of Islamic law to provide legal clarity for children after li'an. This research is a desk research using analytical descriptive method and content analysis, by collecting and analyzing the views of Sheikh Yusuf Al-Qaraḍawi from various reliable sources, including his fatwas and relevant writings. The article includes a brief overview of the concept of li'an and the importance of establishing correct parentage in Islamic law to serve as a benchmark in analyzing the establishment of parentage through DNA testing. The analysis shows that Sheikh Yusuf al-Qaraḍawi supports the use of DNA testing in Li'an cases to establish the child's parentage, provided that the request comes from the wife. This approach protects the wife's right to privacy while utilizing modern technology to achieve justice. The contribution of his thoughts in the reform of Islamic family law in Indonesia is significant, allowing sharia courts to adopt DNA testing, improving accuracy and fairness, and paying attention to the protection of individual rights and family welfare in the contemporary context.Keywords: Li'an, Child's Nasab, DNA Test, Sheikh Yusuf Al-Qaraḍawi, Islamic Law